Integrated historical and religious tourism model of Syech Quro's tomb complex in Karawang Regency, West Java Province, Indonesia - Sri Mariati; Myrza Rahmanita; Rahmat Ingkadijaya; Fachrul Husain Habibie (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2023)
The background of this research is Karawang Regency has various tourism potentials, one of which is historical and religious tourism of Syech Quro's Tomb. One of the important phenomena of the existence of Sheikh Quro's Tomb is the relatively high number of visits, even during the pandemic there were still many tourists visiting and it has increased again after the pandemic. The purpose of the research is to build an integrated historical and religious tourism model at the Syech Quro Tomb Complex in Karawang Regency, West Java Province. The research method used to build the model uses a Participatory prospective analysis which begins by selecting and taking the driving factors and determinants with judgment from experts. The results of this study place agro-tourism development factors as determining factors or driving the success of the integrated and reorganized religious tourism model, institutional strengthening programs, inter-agency relations, local community involvement, incentive funding, and culinary tourism as driving factors for the success of this model. This model is a powerful intervention on ongoing factors. This intervention was carried out in an integrated manner based on the consideration of the need to make integrated tourism at the Syech Quro Tomb Complex a model that must consider economic, social, and ecological sustainability and all village communities support this integrated tour because the benefits can be felt by all surrounding village communities.